Comparison of the Trachea in Normocephalic versus Brachycephalic Cats on the Basis of CT-Derived Measurements - Anna Brunner; Julius Underberg; Jeannette Zimmermann; Simona Vincenti (Veterinary Sciences, 2023)
Tracheal hypoplasia is a major concern in brachycephalic dogs, but there is no consensus for the trachea in brachycephalic cats. We aimed to compare tracheal length and diameter between normo- and brachycephalic cats using computed tomography (CT) image measurements and evaluate their usefulness in tracheostomy planning. A total of 15 normocephalic and 14 brachycephalic cats were included in the study. Tracheas of normocephalic cats were significantly longer compared with brachycephalic cats. No difference was detected in tracheal diameter between normocephalic and brachycephalic cats. Both groups had a lateral diameter significantly larger than the dorsoventral diameter at the level of the cranial end of the manubrium sterni and at the level of the second rib. Normocephalic and brachycephalic cats’ tracheas have the same dorsoventral flattening at the level of the cranial end of the manubrium sterni and at the level of the second rib. The location between the 4th and 5th cervical vertebrae seems the best place to perform a tracheostomy in cats due to its round shape and easily accessible anatomical location. No sign of tracheal hypoplasia in brachycephalic cats was detected. Finally, 7 mm appears to be an adequate diameter for the tracheal tubes used to perform feline tracheostomies.